2019
DOI: 10.1186/s40816-019-0114-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of total phenols, flavonoids and antioxidant activity of various crude extracts of Hyoscyamus gallagheri traditionally used for the treatment of epilepsy

Abstract: Background: Most of the locally available medicinal plant is used as medicine through different ways since the ancient time. Hyoscyamus gallagheri (H. gallagheri) is one of the rare medicinal plant which is indigenous to Oman as well as Gulf countries. The main target of this study is to estimate the total phenols and flavonoids content and evaluate the antioxidant activities of the aerial parts extracts which were collected from the southern part of Oman. Methods: Initially, the powder of aerial parts of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Figure 3 shows the plots between antioxidant activity and phenol contents, which displayed a good pattern against TPC, suggesting the dependence of D. latifolia on TPC for effectiveness (3a), while Figure 3b and 3c were resulted in random plots. This relationship is in agreement with several prior studies (Eddebbagh et al 2016;Guedes et al 2017;Amamra et al 2018;Hossain et al 2019).…”
Section: Correlation Between Phenol Contents and Antioxidant Activitysupporting
confidence: 93%
“…Figure 3 shows the plots between antioxidant activity and phenol contents, which displayed a good pattern against TPC, suggesting the dependence of D. latifolia on TPC for effectiveness (3a), while Figure 3b and 3c were resulted in random plots. This relationship is in agreement with several prior studies (Eddebbagh et al 2016;Guedes et al 2017;Amamra et al 2018;Hossain et al 2019).…”
Section: Correlation Between Phenol Contents and Antioxidant Activitysupporting
confidence: 93%
“…(1) Test for Total Flavonoid Contents (TFC). Following the established colorimetric method with few modifications, the TFC was estimated in different extracts of D. malabarica using quercetin as standard described by Hossain et al (2019). 5 mg of each plant extract was added in 4 mL of methanol in volumetric flask (5 mL).…”
Section: Quantitative Screening Of Phytochemicalsmentioning
confidence: 99%
“…Total flavonoid contents of all tested plant extracts were determined by calibration curve of quercetin standard, and the attained results of TFC were expressed as quercetin equivalents ( μ g quercetin/mg dry sample). All the estimation for TFC investigation in the extracts was done in triplicates [ 30 ].…”
Section: Experimental Datamentioning
confidence: 99%
“…According to the results of composition analysis, we found that the types and contents of polyphenols in MCLW were significantly higher than those in MCLE. The structure of (±)-3′,4′-Methylenedioxy-5,7-dimethylepicatechin is very similar to the structure of catechin, so (±)-3′,4′-Methylenedioxy-5,7-dimethylepicatechin may function like a catechin analog, leading to the activation of AMPK, which suppresses the expression of genes encoding enzymes and transcription factors involved in adipogenesis and lipogenesis, and stimulates those involved in lipolysis [ 36 , 37 ]. This is consistent with our findings, as M. charantia extracts showed significant fatty acid metabolism regulating capacity.…”
Section: Discussionmentioning
confidence: 99%